A new species of Cnemaspis Strauch (Squamata: Gekkonidae) of the C. siamensis group from Tenasserim Mountains, Thailand - Grismer, L. Lee; Yushchenko, Platon V.; Pawangkhanant, Parinya; Nazarov, Roman A.; Naiduangchan, Mali; Suwannapoom, Chatmongkon; Poyarkov, Nikolay A. (Zootaxa, 2020)
An integrative taxonomic analysis recovered the new species Cnemaspis selenolagus sp. nov. of the C. siamensis group as the sister species to C. punctatonuchalis. The new species was discovered in mountain evergreen tropical forests of in Suan Phueng District of Ratchaburi Province, western Thailand. Additionally, the analysis recovered a deep genetic divergence between northern and southern clades within the C. siamensis group that occur on opposite sides of the Isthmus of Kra—a well-known biogeographic region of cladogenic turnover. The description of C. selenolagus sp. nov. brings the total number of species of Cnemaspis in Thailand to 16, 11 of which compose the C. siamensis group—a lineage endemic to the Thai-Malay Peninsula. This underscores the physiographic complexity of this narrow peninsula in that it can support a large number of closely related species in only the northern two-thirds of its length.